2022
DOI: 10.1002/slct.202104137
|View full text |Cite
|
Sign up to set email alerts
|

A NIR‐light‐driven Black Phosphorus Based Nanocomposite for Combating Bacteria

Abstract: Nanocomposites of semiconducting two‐dimensional (2D) materials provide advantageous for combating bacterial infections to overcome antibiotic resistance. In this study, the nanocomposites of 2D black phoshorus (BP) and silver nanoparticles (NPs) were prepared by anchoring as‐synthesized Ag NPs on few‐layer BP nanosheets via liquid self‐assembly method and used as a NIR‐light‐driven antibacterial agent against Gram‐negative bacteria (Escherichia coli and Pseudomonas aeruginosa), and Gram‐positive bacteria (Ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 51 publications
3
14
0
Order By: Relevance
“…The TEM image in Figure 1c reveals two distinct size ranges of Ag NPs, with an average particle size ranging from 4 to 9 nm. The as‐synthesized Au and Ag NPs were then successfully anchored onto the FLBP using a liquid‐phase self‐assembly technique [29] . resulting in the formation of BP/Au and BP/Ag nanocomposites.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The TEM image in Figure 1c reveals two distinct size ranges of Ag NPs, with an average particle size ranging from 4 to 9 nm. The as‐synthesized Au and Ag NPs were then successfully anchored onto the FLBP using a liquid‐phase self‐assembly technique [29] . resulting in the formation of BP/Au and BP/Ag nanocomposites.…”
Section: Resultsmentioning
confidence: 99%
“…Pristine BP nanosheets, BP/Ag and BP/Au nanocomposites were synthesized and fully characterized by our group as previously described. [11,29] Initially, bulk BP crystals were synthesized by using the vapor transport method and later transformed into few-layer black phosphorus (FLBP) through the ultrasoundassisted exfoliation in deoxygenated water. Transmision electron microscopy (TEM) images of pristine BP in Figure 1a revealed that the resulting dispersion possesses a thin layered 2D structure.…”
Section: Synthesis and Characterization Of Bp Nanosheets Bp/ag And Bp...mentioning
confidence: 99%
See 3 more Smart Citations